In vitro targeting of Polo-like kinase 1 in bladder carcinoma: Comparative effects of four potent inhibitors - Brassesco, María Sol; Pezuk, Julia Alejandra; Morales, Andressa Gois; De Oliveira, Jaqueline Carvalho; Roberto, Gabriela Molinari; Da Silva, Glenda Nicioli; De Oliveira, Harley Francisco [UNESP]; Scrideli, Carlos Alberto; Tone, Luiz Gonzaga (Taylor & Francis, 2013)
Despite the improvements in neoadjuvant chemotherapy, the outcome of patients with advanced bladder cancer has changed very little over the past 30 years. In the present study we tested and compared the in vitro antitumor activities of four different inhibitors of Polo-like kinase 1 (PLK1) (BI 2536, BI 6727, GW843682X, and GSK461364), against 3 bladder carcinoma cell lines RT4, 5637 and T24. The impact on radiosensitivity and drug interactions in simultaneous treatments with cisplatin, methotrexate, and doxorubicin were also investigated. Our results showed that PLK1 inhibition prevented cell proliferation and clonogenicity, causing significant inhibition of invasion of tumor cells, though modest differences were observed between drugs. Moreover, all PLK1 inhibitors induced G2/M arrest, with the subsequent induction of death in all 3 cell lines. Drug interactions studies showed auspicious results for all PLK1 inhibitors when combined with the commonly used cisplatin and methotrexate, though combinations with doxorubicin showed mostly antagonistic effects. Comparably, the four PLK1 inhibitors efficiently sensitized cells to ionizing radiation. Our findings demonstrate that irrespective of the inhibitor used, the pharmacological inhibition of PLK1 constrains bladder cancer growth and dissemination, providing new opportunities for future therapeutic intervention. However, further laboratorial and preclinical tests are still needed to corroborate the usefulness of using them in combination with other commonly used chemotherapeutic drugs. © 2013 Landes Bioscience.
Keywords: Bladder cancer; Cell lines; PLK1 inhibition; 4 (8 cyclopentyl 7 ethyl 5,6,7,8 tetrahydro 5 methyl 6 oxo 2 pteridinylamino) 3 methoxy n (1 methyl 4 piperidinyl)benzamide; cisplatin; doxorubicin; gsk 461364; gw 843682x; methotrexate; polo like kinase 1; protein serine threonine kinase inhibitor; unclassified drug; volasertib; antineoplastic activity; antiproliferative activity; bladder carcinoma; cancer cell culture; cancer inhibition; cell death; cell invasion; cell proliferation; clonogenesis; controlled study; drug antagonism; drug potentiation; drug targeting; enzyme inhibition; G2 phase cell cycle checkpoint; human; human cell; in vitro study; ionizing radiation; protein targeting; radiosensitivity; radiosensitization; tumor cell; tumor invasion